Francisco de Osuna and the Spirit of the Letter - Calvert, Laura, 1922- (University of North Carolina publications of the Department of Romance Languages., 2019)
This study shows how Osuna uses mystical symbolism and allegory in his own writing and in the methods of meditation and contemplation he teaches.